Healing Estranged Sorrows Through Re-Visioning Soul-Work - Daniel Boscaljon (Religions)
This article defines estranged sorrow as a category of trauma that cannot be grieved because it was never consciously experienced. As a domain of grief prevented from moving into conscious awareness, estranged sorrow becomes an underlying, chronic source of unspeakable sorrow that diminishes the ability to experience the full range of psychic reality or potentiality. Estranged sorrow encompasses not having developmental psychological needs met, the absence of community, the presence of structural injustice, and the dwindling access to the numinous. Accounting for estranged sorrow beneath a variety of pathologized symptoms shows how the absence of soul and imagination accounts for an addiction to numbing as well as the epidemic of loneliness through a loss of self and social modes of awareness—and thus relationality. I then look to the importance of imaginal revisioning, part of the methodology of archetypal psychology, to better understand and begin working through trauma unearthed by exploring estranged sorrow. The process of revisioning involves the soul-work of personifying the world, seeing through the literal ideas that limit our access to psychic reality, enduring the feelings that something is wrong, and returning to an expanded psychic reality. This article concludes by reflecting on this process in the light of myth.